2017
DOI: 10.1016/j.mattod.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

4D printing of polymeric materials for tissue and organ regeneration

Abstract: Four dimensional (4D) printing is an emerging technology with great capacity for fabricating complex, stimuli-responsive 3D structures, providing great potential for tissue and organ engineering applications. Although the 4D concept was first highlighted in 2013, extensive research has rapidly developed, along with more-in-depth understanding and assertions regarding the definition of 4D. In this review, we begin by establishing the criteria of 4D printing, followed by an extensive summary of state-of-the-art … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
178
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 332 publications
(188 citation statements)
references
References 105 publications
0
178
0
Order By: Relevance
“…The shape memory effect provides a programmed control over both dynamic topography and dynamic internal stress, which is released automatically from the polymer as the object is transformed between different geometrical structures. [ 22 ] The incorporation of topographical features and mechanical force to form a dynamic microenvironment may be the most effective approach to precisely guide stem cell differentiation toward the desired cell lineage. Figure a shows a typical shape change process of thermoset SMPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape memory effect provides a programmed control over both dynamic topography and dynamic internal stress, which is released automatically from the polymer as the object is transformed between different geometrical structures. [ 22 ] The incorporation of topographical features and mechanical force to form a dynamic microenvironment may be the most effective approach to precisely guide stem cell differentiation toward the desired cell lineage. Figure a shows a typical shape change process of thermoset SMPs.…”
Section: Resultsmentioning
confidence: 99%
“…4D fabrication is a highly innovative, next generational additive manufacturing process which can be used to fabricate predesigned self‐assembly structures with a time‐dependent dynamic shape change. [ 22,23 ] Within the diverse 4D mechanisms, shape memory polymers (SMPs) have attracted particular attention owing to their reversible “temporary‐permanent” thermomechanical reprogramming characteristics. [ 24,25 ] Based on our previous experience in 4D fabrication, [ 24,26,27 ] it was expected that the addition of the 4th dimension (time) would benefit the field of neural tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Using the microplates without the flexible joint, hollow microstructures such as a cube can be self‐folded (Figure c). 3D printing of porous bioscaffolds shows tremendous potentials for soft tissue reconstruction . Kang et al reported an integrated tissue–organ printer (ITOP) that can fabricate stable, human‐scale tissue constructs of any shape.…”
Section: D Printing Of Multifunctional Materialsmentioning
confidence: 99%
“…In addition, novel molecular designs, such as double network, can be adopted to achieve robust mechanical properties . Specific to tissue and organ regeneration applications, biocompatible, biodegradable, and physiological environment adaptive hydrogels or other soft materials could be the focus for 4D bioprinting processes . LCE is also a promising material due to its reversible shape‐changing capability.…”
Section: Perspective and Outlookmentioning
confidence: 99%
See 1 more Smart Citation